Revision of the African cichlid fish genus Ctenochromis (Teleostei, Cichliformes), including a description of the new genus Shuja from Lake Tanganyika and the new species Ctenochromis scatebra from northern Tanzania - Genner, Martin J.; Hsu, Ling-Lan; Collins, Rupert A.; Smith, Alan M.; Saxon, Andrew D.; Shechonge, Asilatu H.; Ngatunga, Benjamin P.; Turner, George F. (European Journal of Taxonomy, 2022)
Molecular phylogenetic evidence clearly resolves the African cichlid fish genus Ctenochromis, as defined by Greenwood (1979), as paraphyletic. Here, we redefine the genus Ctenochromis and assign Ctenochromis horei, a member of the Tropheini from Lake Tanganyika, to a new genus Shuja gen. nov. We restrict Ctenochromis to Ctenochromis pectoralis and Ctenochromis scatebra sp. nov., both of which are endemic to the Pangani River catchment in northern Tanzania, and are resolved as sister taxa in a phylogenetic analysis using genome-wide data. Ctenochromis pectoralis is the type species of the genus and described from specimens collected near Korogwe, Tanzania. The species was declared extinct in a 2016 IUCN Red List Assessment. We confirm the continued presence of a population of C. pectoralis within the Ruvu tributary linking Lake Jipe to Nyumba ya Mungu Reservoir. The new taxon Ctenochromis scatebra sp. nov. is described from Chemka Springs, and recognised on the basis of differences from C. pectoralis in tooth and jaw morphology.